TIJIRIT GOLD ORES DISTRICT IN MAURITANIA - MYKHAILOV, Volodymyr; VIRSHYLO, Ivan; ZAGNITKO, Vasyl; KRAVCHENKO, Dmytro; DUBYNA, Oleksandr; SUKACH, Vitaliy; CHULKOV, Sergii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The distribution of a new gold ore district in the Republic of Mauritania – Tijirit, which is associated with the greenstone belt (GSB) of Sebkhet Nich of submeridional extension, is substantiated. It is located 25–30 km to the east of the Reguibat GSB, where the large Tasiast gold deposit is known. The coincidence of the structural position of these two objects and direct signs of gold ore mineralization in the territory of the Tijirit ore district in the form of contrasting lithochemical anomalies of gold, grab sample and trench sample with an increased gold content make it possible to highly evaluate the prospects of its gold ore mineralization. In the ore district, four submeridional to north-northeast trending ore-bearing zones have been identified, within which a number of gold occurrences have been established: Sophie-I, II, III, Lily, Eleonore, Eleonore East, Salma. They coincide with the weakened zones of the same direction, as a rule, they are confined to the contacts of rocks of different composition (metabasalts, metasandstones, banded iron formations, granites), stand out on space image, in geophysical fields, and control the placement of mineralization zones. Of these zones, the most interesting for further geological exploration works is the relatively poorly studied Eastern mineralization zone, which is confined to the contact of the Salma granites and the metabasites of the eastern wing of the Sebkhet Nich GSB. It is associated with the Eleonore East and Salma gold occurrences, numerous lithochemical anomalies, grab, trench and core samples with increased gold content (up to 42–100 g/t). It is recommended to concentrate further geological exploration work within this zone. A number of gold deposits in Ukraine (Sergiivske, Balka Shiroka, Balka Zolota, Surozke) are also associated with the Mesoarchean greenstone structures of the Ukrainian Shield. We hope that the experience of studying gold ore objects in West Africa will help to conduct an objective assessment of gold ore objects in Ukraine.
Keywords: gold ore district; greenstone belt; gold content; metabasites; banded iron formations; granites